Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Economic and Environmental Concept of Food Development in Russia - KOZLOV, Vladimir; POLTARYKHIN, Andrey; VASYUTKINA, Lidia; PONOMAREV, Vladimir; FILIPPOVA, Olga; POPKOV, Sergey (Journal of Environmental Management and Tourism, 2020)
At present, the Russian economy is developing in the conditions of imposed sanctions on high-tech means of production by foreign countries. In this situation, the development vector is the formation of import substitution policies and the solution of food safety issues for various types of food products that are strategically important for human life. Meeting the needs of the country's population with its own production is a priority for the development of the agrarian market, which makes it possible to develop the production agrarian sector, the processing and trade sphere, to create additional jobs, thereby improving the quality and standard of living of people.